(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Chronic recurrent aphthous stomatitis (CHAS) remains one of the urgent problems of practical dentistry, which is confirmed by its high prevalence and lack of effectiveness of treatment methods. With inflammatory pathology of the genitourinary tract, clinic and course, pathological processes in the oral cavity are characterized by the appearance of aphthae, occurring with periodic remissions and frequent exacerbations. In the mucous and submucous membranes of the oral cavity of patients, a violation of immunological parameters, microbiological flora and atypical manifestations of the primary and secondary damaging elements of the mucous membrane are detected. The age of such patients often ranges from 20 to 40 year old patients, and before puberty, persons of both sexes are equally affected, according to the author (Pindbord data) women prevail among adult patients